Pedagogical strategy to compensate for technological addictions from Physical Education in Basic Secondary (Original) (Revista científica Olimpia, 2021)
New technologies hide a potential health risk. In recent years, several so-called technological diseases or addictions have arisen, derived from the inappropriate or indiscriminate use of the computer, mobile phone, video games and others. In this sense, this research was developed in the basic secondary education of the city of Holguín, with the aim of designing a pedagogical strategy based on a set of sports activities that allows compensating the technological addictions present in seventh and eighth grade schoolchildren. By applying the strategy, it was possible to increase the teachers' knowledge about the meaning of ICTs. The mode of action of teachers and students, their interpersonal relationships, and motivation towards the efficient and appropriate use of time were improved. The conclusions constitute generalizations for the achievement of the proposed objective. The recommendations are actions based on raising awareness among teachers and students of Basic Secondary School about the importance of sports activities to compensate for the manifestations caused by technological addictions.
Keywords: sports activities, technological addictions, pedagogical strategy.